Deregulacija i liberalizacija zračnog prometa u Evropi i Jugoslaviji - Mirko Tatalović (Promet - Traffic&Transportation, 1970)
The author deals with the history of efforts within the EC concerning the process of deregulation or liberalization of air transport in Europe, as for the most significant activity taken he refers to the Package of Measures in Air Transport of the Commission for Civil Aviation of 1987. In conjunction with providing the information on transport volumes reported by the airlines and airports in Yugoslavia the author pleads for the elimination of bilateral restrictions, protection of the interregional transport, right of salvage and abandonment, as well as other restrictions in opposition to the proclaimed liberalization.